2009
DOI: 10.1071/en09007
|View full text |Cite
|
Sign up to set email alerts
|

Antimony in the environment: knowns and unknowns

Abstract: Environmental context. Antimony first attracted public attention in the mid-1990s amid claims that it was involved in Sudden Infant Death Syndrome. A substantial number of papers have now been published on the element and its behaviour in the natural environment. However, many key aspects of the environmental chemistry of antimony remain poorly understood. These include critical areas such as its ecotoxicology, its global cycling through different environmental compartments, and what chemical form it takes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
138
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 310 publications
(151 citation statements)
references
References 104 publications
2
138
0
2
Order By: Relevance
“…Worldwide, Sb is the ninth most mined metal and its compounds are listed as priority pollutant by the US Environment Protection Agency (USEPA, 1979). In soils Sb concentrations may be high, due to improperly disposed mine tailings and waste rocks (Filella et al, 2009a(Filella et al, , 2009cWilson et al, 2010), often by far exceeding reported background values for soils (Filella et al, 2002a;Reimann et al, 2010). Despite high total concentrations, the mobility and bioavailability of Sb is generally low (Casado et al, 2007;Flynn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Worldwide, Sb is the ninth most mined metal and its compounds are listed as priority pollutant by the US Environment Protection Agency (USEPA, 1979). In soils Sb concentrations may be high, due to improperly disposed mine tailings and waste rocks (Filella et al, 2009a(Filella et al, , 2009cWilson et al, 2010), often by far exceeding reported background values for soils (Filella et al, 2002a;Reimann et al, 2010). Despite high total concentrations, the mobility and bioavailability of Sb is generally low (Casado et al, 2007;Flynn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In general, inorganic Sb compounds were found to be more toxic than organic ones, with Sb(III) more toxic than Sb(V) species (Filella et al, 2002b). In soil solution Sb is mainly present as pentavalent oxyanion, Sb(OH) 6 À (Filella et al, 2009c;Oorts et al, 2008). This is also the dominant form observed in contaminated soils near smelters and at shooting ranges Takaoka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…methylated species)<antimo-nates (Sb(V))<antimonites (Sb(III) (Gebel 1997;He and Yang 1999;Krachler et al 2001;Filella et al 2002), which is similar to arsenic (As) (Susan et al 2010). Since inorganic Sb species are more abundant than organic species in the natural systems (Filella et al 2009), Sb(V) and Sb(III) were used in our experiments. As a waterlogged plant, rice is usually cultivated in an anaerobic and chemically reduced environment (Colmer 2003 (Armstrong 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Review articles Filella et al [13] in their Review discuss the environmental chemistry of Sb, calling for more focussed research, particularly in the areas of ecotoxicology and speciation analysis.They ask that researchers carefully read the primary literature as myths about Sb are being propagated. A further Review from Tschan et al [14] highlights that, although available soil Sb is readily taken up by plants, little is known about the mechanism by which this occurs.…”
mentioning
confidence: 99%